1995
DOI: 10.1074/jbc.270.28.16820
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Medium Pyrophosphate by Soluble Mitochondrial F1 through Dimethyl Sulfoxide-Water Transitions

Abstract: Soluble F1 from heart mitochondria incubated in mixtures that have Mg2+, inorganic phosphate, and dimethyl sulfoxide (40% (v/v)) catalyzes the spontaneous synthesis of ATP and pyrophosphate (Tuena de Gómez-Puyou, M., García, J. J., and Gómez-Puyou, A. (1993) Biochemistry 32, 2213-2218). By filtration techniques, it was determined that synthesized ATP and pyrophosphate are enzyme bound, albeit the affinity for pyrophosphate was lower than that of ATP. After ATP and pyrophosphate were formed in dimethyl sulfoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…ATP was not formed when the enzyme was in 30 % (v\v) DMSO. This contrasts with the published behaviour of the F " -ATPase [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]31]. The exchange of exogenous phosphate into bound phosphate, the phosphate-ATP exchange reaction and the formation of ATP in a DMSO-free buffer were insensitive to azide.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…ATP was not formed when the enzyme was in 30 % (v\v) DMSO. This contrasts with the published behaviour of the F " -ATPase [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]31]. The exchange of exogenous phosphate into bound phosphate, the phosphate-ATP exchange reaction and the formation of ATP in a DMSO-free buffer were insensitive to azide.…”
Section: Discussioncontrasting
confidence: 53%
“…The remaining four molecules of phosphate could be bound at the two unoccupied nucleotide-binding sites. That two molecules of phosphate can occupy a single nucleotide-binding site is suggested by the work of Tuena de Gomez-Puyou et al [17,18], who found that pyrophosphate was made by F " in the presence of DMSO. However, it is also possible that some phosphate is bound at other, non-nucleotide-binding, sites.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations